Phonological Interference of the Indonesian Language on the Pronunciation of Arabic Hijaiyah Phonemes in the Early Stages of Quran Learning: Psycho-Phonological Analysis in Kindergarten Students - Muhammad Nashi Huddin Ubaidillah; Rafli Maulana Nst; Khayyarah Alimah; Nabila Ramadhan; Nursukma Suri (JURNAL AT-TURAS, 2026)
This study examines the phonological interference of Indonesian language on the pronunciation of Arabic hijaiyah phonemes in kindergarten children in Iqra learning. The purpose of the study is to identify forms of phonological interference and explain the psycho-phonological factors behind them. The approach used is descriptive qualitative with a psycho-phonological framework that operationalizes Chomsky's theory of mental representation, Weinreich's interference theory, and Lado's contrastive analysis as analytical instruments. Eight students from Ibnu Al-Akbar Lubuk Pakam Kindergarten who are taking Iqra volume 1 were selected through purposive sampling based on the criteria of native Indonesian speakers who have not received formal tajweed training. Data were collected through pronunciation tests, voice recordings, classroom observations, and phonological discrimination tests. The results showed that the Indonesian sound system significantly affected the production of Arabic phonemes in children, especially in emfatic consonants (tafkhim), throat sounds (pharynx and laryngeal), and uvular consonants that are not found in the Indonesian phonological system. Although the average score of the production test of 17.25 out of 20 indicates a fairly good basic ability, analysis of the sound discrimination test reveals that a number of pronunciation errors stem from the limitations of phonological perception, rather than mere articulation weaknesses. The error pattern was dominated by sound substitution (26 cases), followed by changes in sound properties (10 cases) and sound elimination (4 cases). These findings contribute to the understanding of the mechanisms of second language phonological adaptation in early childhood, which in the framework of the Perceptual Assimilation Model (Best and Tyler, 2007) can be described as a perceptual assimilation process in which unfamiliar second language sounds are assimilated into the most similar categories of first language phonemes and form the basis of recommendations for Iqra learning strategies based on multisensory approaches and auditory discrimination training.